Mitigating the Distributed Denial of Service (DDoS) Attacks in Campus Local Area Network(CLAN) - Sen, Angshu Maan; Singha, K. Anand Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Campus Local Area Network (CLAN) of academic institutions interconnect computers ranging from one hundred to about twenty five hundred and these computers are located in academic building(s), hostel building(s), faculty quarter(s), students amenities centre, etc all around the campus. The students, faculty and the supporting staff members use the network primarily for internet usage at both personal and professional levels and secondarily for usage of the available services and resources. Various web based services viz: Web Services, Mail Services, DNS, and FTP services are generally made available in the campus LAN. Apart from these services various intranet based services are also made available for the users of the LAN. Campus LAN users from the hostels change very frequently and also sometime become targets (we call as soft targets) to the attackers or zombie because of either inadequate knowledge to protect their own computer/ laptop, which is also a legitimate node of the campus LAN; or their enthusiastic nature of experimentation. The interconnectivity of these legitimates nodes of the campus LAN and that of the attackers in the World Wide Web, make the computers connected in the LAN (nodes) an easy target for malicious users who attempt to exhaust the resources by launching Distributed Denial-of-Service (DDoS) attacks. In this paper we present a technique to mitigate the distributed denial of service attacks in campus wide LAN by limiting the bandwidth of the affected computers (soft targets) of the virtual LAN from a unified threat management (UTM) firewall. The technique is supported with help of bandwidth utilization report of the campus LAN with and without implementation of bandwidth limiting rule; obtained from the UTM network traffic analyzer. The graphical analyzer report on the utilization of the bandwidth with transmitting and receiving bits of the campus LAN after implementation of our bandwidth limiting rule is also given.